Stargirl. The complete first season [videorecording (DVD)]. - Bassinger, Brec, 1999-; Monreal, Yvette, 1992-; Washington, Anjelika, 1998-; Gellman, Cameron, 1998-; Johns, Geoff, 1973- (Warner Bros. Home Entertainment, 2020)
After discovering the original Star-Spangled Kid's gear, teenager Courtney Whitmore joins the Justice Society of America as Stargirl, teaming up with her stepfather Pat Dugan in his robotic exosuit. Based on the DC Comic Stars and S.T.R.I.P.E.